Cytotoxicity and genotoxicity of untreated hospital effluents - Ortolan,Maria da Graça Silva (2007)
Untreated hospital effluent samples were tested for cytotoxic and genotoxicity in order to access whether they presented any serious health hazards. Results of umuC test suggested that the effluent from a large, general hospital could be considered weakly genotoxic. Comparatively, effluents from inpatient units presented higher frequency of genotoxicity than those coming from laboratory facilities. Although no cytotoxic activity was detected in laboratory effluent samples, cytotoxicity appeared to be an important problem of effluents from inpatient units.